2014
DOI: 10.1007/s11517-014-1235-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intraluminal thrombus on noninvasive abdominal aortic aneurysm wall distensibility measurement

Abstract: Abdominal aortic aneurysm wall distensibility can be estimated by measuring pulse pressure and the corresponding sac volume change, which can be obtained by measuring wall displacement. This approach, however, may introduce error if the role of thrombus in assisting the wall in bearing the pulse pressure loading is neglected. Our aim was to introduce a methodology for evaluating and potentially correcting this error in estimating distensibility. Electrocardiogram-gated computed tomography images of eleven pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Specifically, Meyer et al [28] have shown that thrombus can have a stress-reducing role even if it does not directly reduce pressurization of the wall, when thrombus is assumed to be fully attached to the wall. It has recently been shown that the wall distensibility, as measured by sac volume change and pulse pressure, should be corrected using a correction factor that includes thrombus percentage in the sac [29]. However, its exact role in AAA wall stress has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Meyer et al [28] have shown that thrombus can have a stress-reducing role even if it does not directly reduce pressurization of the wall, when thrombus is assumed to be fully attached to the wall. It has recently been shown that the wall distensibility, as measured by sac volume change and pulse pressure, should be corrected using a correction factor that includes thrombus percentage in the sac [29]. However, its exact role in AAA wall stress has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Most computational numerical analyses of AAA wall stresses that include ILT assume its perfect attachment to the wall (as reported in []). In these cases, it is modelled to be able to bear tensile loads and reduces the load on the wall considerably . If thrombus needs to be considered as a solid that is perfectly attached to the wall, distensibility of the wall itself would be underestimated in this study, where the possible stress shielding role of ILT is disregarded.…”
Section: Limitationsmentioning
confidence: 99%
“…The restricted boundary nodes limited the longitudinal deformation of the aorta model. Although the “almost-true” stress alone can be used in many applications, such as using the stress-based rupture potential index as an aneurysm rupture risk predictor [39], different tissue damage and failure models exist such as accumulated energy [40, 41], stretch based criterion [42] and distensibility [43] which rely on the deformation and thus depend on patient-specific material properties. Previous works in our group [17] showed that the failure pressure of ascending aortic aneurysm was much higher than the measured systolic pressure, and the failure behavior of the aorta were highly correlated with material properties.…”
Section: Discussionmentioning
confidence: 99%